The International Legal Framework Regarding the Romanian Prisoners of War from the Eastern Front in the Second World War - Stefan, Gheorghe (Journal of Danubian Studies and Research, 2023)
The international legal framework regarding prisoners of war, for the first half of the century. XX, had been regulated by the "Regulation concerning the Laws and Customs of War on Land", annexed document to the Fourth Hague Convention of 1907, and the Geneva Convention concerning the Treatment of Prisoners of War of July 27, 1929. The status of prisoners of war The war will be regulated in the content of 97 articles which provided legal obligations for the state that had them in custody regarding the foreign soldiers as well as the rights that the latter had. During the Second World War, the two documents related to international law had a different applicability for the states of the world.